High prevalence of long-term and late effects in a South African childhood cancer survivor cohort - Anel Van Zyl; Sandile Ndlovu; Carl Lombard; Ronelle Uys; Leilah Schoonraad; Paul C. Rogers; Mariana Kruger (EJC Paediatric Oncology, 2023)
Purpose: We documented the prevalence of late effects in a South African childhood cancer survivor (CCS) cohort. Patients and methods: CCSs at Tygerberg Hospital, Cape Town, were evaluated for clinical abnormalities, whereafter late effects were identified, graded according to the Common Terminology Criteria for Adverse Events (CTCAE), and classified as significant or insignificant. Results: The cohort comprised 160 CCSs (median age 13 years (interquartile range 9.9 – 17.8 years); follow-up period eight years (range 5–37.2 years)). There were 89 (55.6%) hematological and 71 (44.4%) solid malignancies. Most CCSs (146/160; 91.3%) had at least one late effect; the majority were of Grade 1 CTCAE severity (73.7%). Common late effects were gastrointestinal (13.3%), metabolic (12.9%), hematological (9.2%), musculoskeletal (9.1%), and neurological (8.8%) disorders. Significant risk factors for late effects were cancer diagnosis (p = 0.005), chemotherapy (moderate intensity [incidence rate ratio (IRR) 1.84; p = 0.036]; high intensity [IRR 2.8; p = 0.001]), and radiotherapy (IRR 1.44) (p = < 0.001). Late effects severity was significantly associated with radiotherapy (IRR 1.54; p = 0.004). Solid tumor survivors were more likely to develop Grade 2 (IRR 2.4; p = < 0.001) and 3 late effects (IRR 2.8; p = 0.011). Conclusion: This is the first prospective study of a CCS cohort in South Africa. Most CCSs developed mild or moderate long-term and late effects, significantly associated with cancer diagnosis, chemotherapy intensity, and radiotherapy. It is crucial to develop long-term surveillance plans for CCSs in South Africa to ensure early detection of late effects.